CORRELATION BETWEEN ORTHODONTIC TREATMENT NEEDS AND PSYCHOSOCIAL CONDITION OF ADOLESCENTS IN SMPN 1 MARABAHAN - Erwan Ridha Muzakki; Diana Wibowo; Nolista Indah Rasyid (Dentino : Jurnal Kedokteran Gigi, 2020)
Background: Malocclusion creates problems in mastication, swallowing, speech, high risk of trauma, periodontal disease, caries and decreased aesthetic which can affect psychosocial. People with malocclusion often receive poor response from others, such as insult or inappropriate nickname. The psychological effects on people with malocclusion include inferiority, embarrassment, difficulty in adaptation, emotional disorder, lack of confidence, uncomfortable social interaction, unhappy, and often compare themselves with others. These will affect a person’s development, especially during adolescence. Objective: The purpose of this research was to know about correlation between the orthodontic treatment needs with the psychosocial condition in adolescent at SMPN 1 Marabahan. Methods: This research was an observational analytic using cross sectional approach. The sample size using Slovin in this research was 76 students of SMPN 1 Marabahan. Data collection was performed using IOTN-DHC and PIDAQ questionnaire. Data analysis consisted of univariate analysis which described each variable and bivariate analysis with Spearman test. Results: The orthodontic treatment needs at SMPN 1 Marabahan based on the highest IOTN-DHC was in the category of really need the treatment. They were about 40 people (53%). The psychological condition in adolescent based on the highest PIDAQ was on the student with an average score of 45.22. Conclusion: There is a significant correlation between orthodontic treatment needs with the psychosocial condition of adolescent.